Gender inequalities in authorship of the main Spanish medical journals in 2017 - Sebastián Tornero Patricio; Inmaculada O. Alonso Rueda; Julia García Gozalbes; José Antonio Domínguez Domínguez; Liliana Charris-Castro; María Dolores González-Soria; María del Mar García Calvente (Elsevier, 2020)
Introduction: Some studies have shown a lower female participation in scientific publications. The objective of this study is to analyse the gender inequalities in the main Spanish journals of medical publications. Material and Method: Cross-sectional study of the main Spanish medical journals classified by SCImago Journal & Country Ranking (n = 24) and their publications (n = 3.375), during the year 2017. Women/men ratio in authorship was calculated for all journals and types of papers. Bivariate analyses were developed with the type of article as the dependent variable,and gender, institution, and country of the first and last authors as the independent variables. Logistic regression models were performed to calculate adjusted odds ratios (aOR) and their 95% confidence intervals (95%CI) of the types of papers according to authorship gender, institution, and country. The statistical program used was R. Results: The total number of authors was 16,252 (44.2% women, 53.9% men, and 1.9% non-identified gender). Women represented 46% of the first authors and 33.5% of the last ones. Women were the first authors of Editorials less often than men (aOR = 0.39; 95%CI = 0.30−0.51), but more often in Originals (aOR = 1.55; 95%CI = 1.33-1.80). Women were the last authors with less frequency in all types of papers, especially in Editorials (aOR = 0.50; 95%CI = 0.35−0.70). The women/men ratio in authorship was less than 0.80 in 10 of 26 journals analysed (41.7%). Conclusions: These results show the gender inequalities in the authorship of the main Spanish medical journals in 2017, especially as first authors and Editorials. Resumen: Introducción: El objetivo del estudio es analizar la desigualdad de género en la producción científica de las revistas médicas españolas. Material y método: Estudio transversal de las principales revistas médicas españolas clasificadas por SCImago Journal & Country Ranking (n = 24) y sus publicaciones (n = 3.375) durante el año 2017. Se calculó la ratio mujer/hombre de autoría según revista y tipo de artículo. Los análisis bivariantes se desarrollaron con la variable dependiente tipo de artículo y las independientes: sexo, centro de trabajo y país de primeras y últimas autorías. Se realizaron modelos de regresión logística para el cálculo de odds ratios ajustadas (ORa) con intervalos de confianza al 95% (IC95%) del sexo de autoría según tipo de artículo, mediante el programa estadístico R. Resultados: El número total de firmantes fue 16.252 (44,2% mujeres, 53,9% hombres y 1,9% sexo no identificado). Las mujeres representaron el 46% de las primeras autorías y el 33,5% de las últimas. Las mujeres fueron primeras autoras de Editoriales con menor frecuencia que los hombres (ORa = 0,39; IC95% = 0,30−0,51), pero con mayor frecuencia en los Originales (ORa = 1,55; IC95% = 1,33−1,80). Las mujeres fueron últimas autoras con menor frecuencia en todos los tipos de artículos, especialmente en Editoriales (ORa = 0,50; IC95% = 0,35−0,70). La ratio mujer/hombre del total de autoras y autores fue inferior a 0,80 en 10 de las 24 revistas analizadas (41,7%). Conclusiones: Se demuestra la desigualdad de género en la autoría de las principales revistas médicas españolas en el año 2017, principalmente en las últimas autorías y los Editoriales.